Tropical fruits of mango and noni having dual effects of coagulating milk and enriching the curds with micro-constituents of medicinal potential - Jaya Vejayan, Palliah; Norliana, Munir; Yee, Lee Lian; Rupbansraaj, Bathmanathan; Halijah, Ibrahim; Srikumar, Chakravarthi (University of Malaya, 2019)
Plants are capable ofcoagulating milk efficiently and enriching the curd with medicinal potentials, which can result in an ideal functional dairy food. Such efforts were attempted within this study with two fruit bearing plants, Mango (Mangifera indica)and Noni (Morinda citrifolia).The extracts of the two plants were separated to their enzymatic fractions and investigated for their coagulating timein comparison to rennet enzyme of Mucor miehei. The biological activities of the curd formed by the extracts were evaluated to determine the antioxidant and antidiabetic activities. The coagulation of milk by M.indicaseed fraction,M.citrifoliafruit fraction and the rennet (15%, 15%, and 5% (w/v), respectively) resulted in coagulation timesof 10.8 ± 0.36 s, 40.73 ± 1.91 s and 198.2 ± 1.01 s, respectively. Curd by aqueous extract of M. indicaseeds resulted inthemost favourablevalues: IC50=3.266 ± 0.353μg/mL(2,2-diphenyl-1-picylhydrazyl, DPPH), 147.329 ± 1.890 mg GAE/g (Ferric Reducing Antioxidant Power, FRAP), IC50= 17.87 ± 0.415 μg/mL (α-glucosidase inhibition) and IC50= 41.87 ± 0.585μg/mL (α-amylase inhibition).Hence, M. indicaseed and M. citrifoliafruit extracts weretested, and both plant extracts, together with curd-fortification, exhibiteduseful biological activities